2016
DOI: 10.5539/ibr.v9n10p186
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Behavior: Relations with Developmental Culture, Psychological Empowerment, Distributive Justice and Organizational Learning Capacity

Abstract: Competitive advantage has a significant role in organizations' survival and the key path to achieve that advantage passes through innovation. Organizations need employees who do not just create new ideas but also implement them. These innovative behaviors may provide great contributions to both organizational performance and success. There are certain factors which motivate employees to exhibit such behaviors. Concordantly, the present study aims to discover how innovative behaviors of employees are related wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 54 publications
1
7
0
2
Order By: Relevance
“…It has been found in this study that there is no significant impact of distributive justice on the innovative work behavior of employees working in the organizations as there is no impact of distributive justice on the innovation of employees has been found in this specific study. However, the previous studies conducted by Gozukara & Yildirim (2016); Momeni et al, (2014); Hsu & Wang, 2015& Janssen (2000 state that there is a significant relationship between distributive justice and employee innovative work behavior. These studies focused that the distributive justice is essential to be followed in the organizations in order to make the behavior of employees positive and to direct them towards bringing innovation in their work.…”
Section: Discussion and Implementationmentioning
confidence: 94%
See 1 more Smart Citation
“…It has been found in this study that there is no significant impact of distributive justice on the innovative work behavior of employees working in the organizations as there is no impact of distributive justice on the innovation of employees has been found in this specific study. However, the previous studies conducted by Gozukara & Yildirim (2016); Momeni et al, (2014); Hsu & Wang, 2015& Janssen (2000 state that there is a significant relationship between distributive justice and employee innovative work behavior. These studies focused that the distributive justice is essential to be followed in the organizations in order to make the behavior of employees positive and to direct them towards bringing innovation in their work.…”
Section: Discussion and Implementationmentioning
confidence: 94%
“…The findings conducted in this study are quite different from these previous studies conducted in the similar study area by the previous researchers. But there are also some previous studies conducted on the impact of organizational justice and employee positive behavior that include the study conducted by Gozukara & Yildirim (2016); Ismail et al (2019) showed an insignificant relationship between distributive justice in organizations and the employee innovative working behavior. This study focused that there is no impact of distributive justice on the innovative working behavior of employees working in the organizations and the innovation factor does not get affected by it.…”
Section: Discussion and Implementationmentioning
confidence: 99%
“…It has been found in this study that there is a significant impact of distributive justice on the idea realization of employees working in the organizations. However, the previous studies conducted by Gozukara, Yildirim, Yildiz, et al (2016), Jiun-Lan and Jeng-Hwan ( 2015) Janssen (2000), and Momeni, Ebrahimpour, and Ajirloo (2014) state that there is a significant relationship between distributive justice and employee innovative work behavior. These studies focused that distributive justice is essential to be followed in the organizations to make the behavior of employees positive and to direct them towards bringing innovation in their work.…”
Section: Discussion and Implementationmentioning
confidence: 93%
“…The outcome of the current study is different from the previously conducted studies in the same field. But there are also some previous studies conducted on the impact of organizational justice and employee positive behavior that include the study conducted by Gozukara et al (2016), Ismail (2019), indicated a negative relationship between distributive justice and innovative work behavior.…”
Section: Discussion and Implementationmentioning
confidence: 99%
“…No entanto, conforme Gozukara et al (2016) para que resultados inovadores aconteçam a partir da inovação, não basta sua pré-existência ou autodeterminação do indivíduo em ser inovador, mas se faz necessário uma cultura que possibilite trocas de conhecimento no ambiente em que estão inseridos essas indivíduos. Para Jong e Hartog (2008) resultados inovadores advém de comportamento inovador oriundo do compartilhamentos e trocas que dois antecedentes podem aferecer: liderança participativa e estímulos a trocas com contatos externos.…”
Section: Introductionunclassified